The Financial Development-Environmental Degradation Nexus in Bangladesh: A Long-Run Co-Integration Approach - Khuky, Mahmuda Akter (Energy Economics Letters, 2021)
Using annual time series data from 1983 to 2019, this study examines the impact of economic growth, exports, energy consumption, and financial development on environmental deterioration in Bangladesh. The long-run cointegration of variables is investigated using Dynamic Ordinary Least Squares (DOLS) and Fully Modified OLS (FMOLS) approaches. The co-integration study demonstrates a long-term relationship between dependent variable and independent variables. The findings reveal that in the long run the primary determinants of carbon dioxide emissions are economic growth, energy consumption, export, and financial development are the primary determinants of carbon dioxide emissions. Except for energy consumption, the result shows that financial development, economic development, and export have a statistically significant long-run co-integration with environmental degradation (CO2 emissions and ecological footprint). The Environmental Kuznets Curve, a quadratic term for economic expansion, demonstrates a negative impact on environmental degradation (EKC). The key findings show and emphasize the need for sound policies for more equal economic and financial growth, as well as, environmentally sustainable financial services. According to the findings, the government should prioritize programs that reduce carbon dioxide emissions by strengthening the financial sectors. Also government should consider the role it plays in slowing environmental degradation and hence, directly enhancing environmental quality in Bangladesh.